?ACTIVATION PARAMETERS OF BUTANE AND DECANE SULFONIC ACIDS (Na-SALT) IN PURE AND MIXED SOLVENTS AT DIFFERENT TEMPERATURES BY VISCOSITY MEASUREMENTS - Jabeen, Shaista; Akber, Shagufta; Uddin, Fahim (Biological Sciences - PJSIR, 2000)
The viscosities of the various solutions of I-Butane Sulfonic Acid (Na-SaJt) and l-Decane Sulfonic Acid (Na-Salt) in pure and mixed solventshavebeenmeasured at fourtemperatures 298, 303,308and 313K.The measured data have been used to calculate viscosity coefficients of Jones-Dole equation. These coefficients have been found to be dependent on temperature and solvent composition.The positive valuesofB coefficientsfor butaneanddecane sulfonic acids (Na-salt) in pure and mixed solvents led to the conclusion that ion-solvent interaction is not so strong. Activation parameters such as energy of activation (Ell *), free energy change of activation ( G*) and entropy change of activation ( S*) have been evaluated at different temperatures in pure and mixed solvents.